Alternative Analysis of Flood Control Downstream of Way Sekampung River - Sugito SUGITO; Maulana Febramsyah (International Conference on Engineering and Technology Development (ICETD), 2013)
Downstream part of the watershed is an area of lowland Sekampung with +3.00 to +4.00 elevation above sea level. Area located between the border regions of South Lampung regency and East Lampung. Originally this area was flooded reservoir area, the Swamp Sragi and surrounding areas, but along with the development of this area is used as a residential area, pertaniandan pond area for the people around the area. Padatahun 2002 River Way Sekampung experience overflow caused flooding in downstream areas which suffered losses of up to 38 billion rupiahIn this study analyzed the incidence of flooding that may occur based on rainfall data available. Based on the results of the input stream and cross sectional design flood discharge is seen that when the flood began when the river reaches flood discharge Q50-year anniversary.In this study flood control analysis performed on the three methods are: the construction of levees, making retention ponds and dredge rivers. The third input method results in HEC RAS 3.1.3 shows that building levees to reduce flooding by 32%, on a flood retention pond can be reduced up to 45% and normalization of the river is only able to reduce flooding by 20%. Most effective flood management recommendation is to build two retention ponds and technical cost reduction by flooding.